2022
DOI: 10.3389/fpubh.2022.843622
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of PM2.5 on the Growth Curves of Children's Obesity Indexes: A Prospective Cohort Study

Abstract: AimsTo explore the effect of long-term exposure to particulate matter with an aerodynamic diameter of 2.5 μm or less (PM2.5) on childhood obesity based on a cohort study in Chongqing.MethodsA total of 4,284 children aged 6–8 years at baseline were enrolled from the Chongqing Children Health Cohort in 2014–2015 and were followed up in 2019. A stratified cluster sampling was applied to select the participants. A Mixed-effects linear regression model was used to examine the effect of long-term exposure to PM2.5 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Recently, accumulating research has shown that exposure to PM2.5 can act as an independent factor to disrupt the balance of lipid metabolism (McGuinn et al, 2019;Zhang et al, 2021). Air pollution can increase the BMI of children and can increase the probability of developing obesity, as reported by most epidemiological studies (Tong et al, 2022). The underlying molecular mechanisms, however, are not completely understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, accumulating research has shown that exposure to PM2.5 can act as an independent factor to disrupt the balance of lipid metabolism (McGuinn et al, 2019;Zhang et al, 2021). Air pollution can increase the BMI of children and can increase the probability of developing obesity, as reported by most epidemiological studies (Tong et al, 2022). The underlying molecular mechanisms, however, are not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Recently accumulating epidemiological studies have supported the link between air pollution and obesity ( Dong et al, 2014 ; Li et al, 2015b ; Rohde and Muller, 2015 ). For instance, prenatal exposure to air pollution or childhood exposure to traffic pollution increases BMI and contributes to the development of obesity ( Fioravanti et al, 2018 ; Tong et al, 2022 ). Consistently, our results show that whole-body PM2.5 exposure leads to significant hypertrophy of white adipose tissue in young mice, including sWAT and gWAT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family history of obesity or CVD was investigated using a self-filled questionnaire. In addition, sleeping quality and dietary intake of vegetables, red meat, and salt were surveyed; the detailed protocol was published in a previous paper[ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…51 In a meta-analysis of 15 studies of air pollution exposure in children, a significant association was found between PM 1 , PM 2.5 , and PM 10 , with a 28% increase in the risk of obesity per 10-µg/m 3 increase in PM 2.5 . 52 Tong et al 53 found that every 5-µg/ m 3 increase in PM 2.5 levels in children 6 to 8 years of age followed for 4 years led to a 26% increase in relative risk of central obesity. In a large cohort of 44 718 children and adolescents aged 7 to 18 years in China, PM 1 , PM 2.5 , PM 10 , and NO 2 were associated with increased body mass index Z score, waist circumference, and waist-toheight ratio, and higher prevalence of general and central Built environment and air pollution make up a key element of one's social determinants of health.…”
Section: Impact On Cardiovascular Risk Factorsmentioning
confidence: 99%